Encountering Dapsone Poisoning In a Child at the Emergency Department of a Tertiary Care Hospital in Eastern Nepal - Malla, Gyanendra; Gauchan, B; Chaudhary, S; Bhandari, R; Gupta, P P (Health Renaissance, 2015)
Dapsone (4, 4’-diaminophenylsulfone), a sulfonamide derivative, was introduced in 1943 as an effective chemotherapeutic agent for leprosy and still is an important drug for the treatment of this disease. Because of its use in various conditions, its toxicity is commonly seen in adults but rare in children. Rapid clinical assessment, measurement of methemoglobin and institution of methylene blue where indicated decreases the morbidity and mortality of dapsone poisoning. We report a case of 2 year old female with accidental ingestion of 20 tablets (20gm) of dapsone. DOI: http://dx.doi.org/10.3126/hren.v12i1.11988 Health Renaissance 2014;12(1):52-54